Development of interactive manipulative motion learning media using adobe animate for elementary school students - Lanos, Muhsana El Cintami; Handyani, Widya; Manullang, Jujur Gunawan; Winartiningsih, Anes; Festiawan, Rifqi (Universitas Negeri Yogyakarta, 2024)
Over the past few years, there has been a growing recognition of the importance of integrating technology into educational practices to engage students more effectively. Traditional PE methods and limited resources have hindered effective learning, necessitating new approaches. This research aimed to develop innovative, interactive learning media based on adobe animate to enhance elementary students' learning outcomes in manipulative movement skills